2017
DOI: 10.11152/mu-923
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of Quasistatic Ultrasound Elastography (USE) compared with Baseline US for parotid gland lesions: preliminary results of elasticity contrast index (ECI) evaluation

Abstract: Aims: To assess the diagnostic value of elasticity contrast index (ECI) elastography, in comparison with conventional ultrasound for the differentiation of benign and malignant parotid lesions. Material and methods: Sixty-three consecutive patients with parotid gland tumors, treated surgically at a single tertiary center were enrolled. Ultrasound evaluation consisted of B-mode, color-Doppler and quasistatic ultrasound elastography (USE), conducted with the ECI technique. For each lesion the echogenicity, margi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Quantitative and shear wave elastography may be promising for differentiation and characterization. Cantisani et al assessed 63 parotid tumors by using the semiquantitative technique for stiffness evaluation. They measured the elasticity indexes and reported that mean elasticity was statistically significant between benign and malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative and shear wave elastography may be promising for differentiation and characterization. Cantisani et al assessed 63 parotid tumors by using the semiquantitative technique for stiffness evaluation. They measured the elasticity indexes and reported that mean elasticity was statistically significant between benign and malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Klintworth et al 2012 [8] Yerli et al 2012 [24] Badea et al 2013 [16] Celebi and Mahmutoglu 2013 [17] Wierzbicka et al 2013 [19] Yu et al 2016 [20] Altinbas et al 2017 [15] Cantisani et al 2017 [7] Herman et al 2017 [6] Mansour et al 2017 [18] 1: Was the spectrum of patient representative of the patients who will receive the test in practice? Recently, several original studies have focused on the value of sonoelastography for differentiating between malignant and benign parotid lesions.…”
Section: Quadas Questionnairementioning
confidence: 99%
“…In addition, haemorrhage and calcification in benign tumours may result in a heterogeneous appearance that resembles a malignancy [1][2][3][4][5]. Although ultrasound-guided fine-needle aspiration cytology (FNAC) is considered the gold standard for preoperative diagnosis [6], it is an invasive method and, as a general rule, non-invasive methods are preferred when the results are similar [7]. Sonoelastography is an innovative diagnostic imaging tool that assesses tissue stiffness [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No external compression with the transducer was needed as Elastoscan uses the pulsations of the carotid artery (in vivo compression) for the elastography response. 5 Patient is instructed to hold breath and swallowing for 10-15 seconds during scan. 6 The image is paused after all the colour bar turned green.…”
Section: Protocol For Thyroid Elastographymentioning
confidence: 99%